Pemberantasan Mafia Hukum di Pengadilan - Putu Tresna Nararya Indranugraha; I Gede Artha (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The purpose of this study is to find out and analyze the occurrence of judicial mafia actions in court institutions and to review and provide solutions to overcome judicial mafia actions in courts. The above phenomena will be studied based on normative legal research. With a statutory approach, a legal concept approach, and a case approach. The analysis used is technical evaluative, argumentative, and descriptive. Problem are studied and analyzed based on theoretical foundations such as legal principles, legal concepts, doctrine, jurisprudence and legal theory. The results of the study explained that the judicial mafia that occurs in Indonesian criminal justice does not only occur in legal courts and law enforcement regarding the judicial mafia that occurs in the courts requires strategies and strict actions for the perpetrators, so far the occurrence of lawlessness by judges is still difficult to control, stemming from low morals, a consumptive lifestyle easily tempted by the lure of bribes, gratification that results in abuse of authority, until it leads to the emergence of legal mafia actions in court Tujuan penelitian ini adalah untuk mengetahui dan menganalisis terjadinya Tindakan mafia peradilan pada Lembaga pengadilan serta mengkaji dan memberi solusi guna mengatasi Tindakan mafia peradilan di pengadilan. Terhadap fenomena diatas akan diteliti berdasar penelitian hukum normatif. Dikaji melalui pendekatan perundang-undangan, pendekatan konsep hukum serta pendekatan kasus. Analisis yang digunakan dengan teknis evaluatif, argumentatif dan deskriptif. Permasalahan dikaji dan dianalisis berdasar Landasan teoritis seperti asas-asas hukum, konsep hukum, doktrin, yurisprudensi dan teori hukum. Hasil penelitian menjelaskan bahwa mafia peradilan yang terjadi dalam peradilan pidana Indonesia bukan saja terjadi di pengadilan hukum serta penegakan hukum menyangkut mafia peradilan yang terjadi di pengadilan memerlukan strategi dan tindakan tegas bagi pelakunya, selama ini terjadinya pelanggaran hukum oleh oknum hakim masih sulit dikendalikan, bersumber dari moral yang rendah, gaya hidup konsumtif dengan mudah tergoda iming-iming suap, gratifikasi yang mengakibatkan penyalahgunaan kewenangan, sampai berujung munculnya tindakan mafia hukum di pengadilan.